Tackling the Most Difficult Problems : Infrastructure, Ebola, and Climate Change - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group states that the infrastructure gap is enormous --an estimated $1 trillion to $1.5 trillion more is needed each year. To fill this gap, the Bank needs to tap into the trillions of dollars held by institutional investors, most of which are sitting on the sidelines, and direct those assets into projects that will have great benefit for a range of developing countries. The Bank announced the creation of the Global Infrastructure Facility, which is designed to attract financing for infrastructure needs. To combat Ebola, the Bank needed to move to an emergency footing. During all of the efforts on infrastructure, Ebola, and climate change, teams from across the institution worked collaboratively and displayed an inspiring commitment to innovation. The Bank will be aggressive and creative and apply large-scale solutions to help states manage, prepare for, recover from and conquer the risks, so they can grow and flourish. The Bank’s strategy on climate change has five parts: carbon pricing, eliminating fuel subsidies, cleaner cities, smart agricultural policies, and renewable energy investment.